2006
DOI: 10.1007/s10637-006-6452-1
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center phase II study of sequential paclitaxel and bryostatin-1 (NSC 339555) in patients with untreated, advanced gastric or gastroesophageal junction adenocarcinoma

Abstract: Sequential paclitaxel plus bryostatin-1 resulted in a superior response rate than would be expected of paclitaxel alone in patients with untreated, advanced gastric or gastroesophageal junction adenocarcinoma. Further development of this combination is warranted once an effective method to ameliorate or prevent myalgias can be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 9 publications
1
52
0
Order By: Relevance
“…First, paclitaxel is considered an effective drug for gastric cancer, with response rates ranging from 20 to 28% in single-agent phase II studies (Ajani et al, 1998;Ohtsu et al, 1998;Yamada et al, 2001;Yamaguchi et al, 2002). Furthermore, Ajani et al (2006a) reported that sequential treatment with paclitaxel and bryostatin-1 is effective, with a response rate of 29%. Paclitaxel is a good candidate for combined treatment because of it lacks crossresistance to fluoropyrimidine derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…First, paclitaxel is considered an effective drug for gastric cancer, with response rates ranging from 20 to 28% in single-agent phase II studies (Ajani et al, 1998;Ohtsu et al, 1998;Yamada et al, 2001;Yamaguchi et al, 2002). Furthermore, Ajani et al (2006a) reported that sequential treatment with paclitaxel and bryostatin-1 is effective, with a response rate of 29%. Paclitaxel is a good candidate for combined treatment because of it lacks crossresistance to fluoropyrimidine derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…However, several phase II studies using bryo-1 alone were disappointing in melanoma, 33 colorectal cancer, 34 and gastric carcinoma. 35 As the application of paclitaxel followed by bryo-1 significantly reduced tumor growth in mice, 36 phase II studies of bryo-1, in combination with other cytotoxic agents, were tried in pancreatic and prostate cancer, and renal cell and gastric carcinoma. 8,10,35 As a result, an enhanced response to paclitaxel by bryo-1 was observed in advanced gastric or gastroesophageal junction adenocarcinoma in phase II studies.…”
Section: Biology and Chemistry Of Bryostatin-1mentioning
confidence: 99%
“…35 As the application of paclitaxel followed by bryo-1 significantly reduced tumor growth in mice, 36 phase II studies of bryo-1, in combination with other cytotoxic agents, were tried in pancreatic and prostate cancer, and renal cell and gastric carcinoma. 8,10,35 As a result, an enhanced response to paclitaxel by bryo-1 was observed in advanced gastric or gastroesophageal junction adenocarcinoma in phase II studies. 35 Similar results were obtained for advanced esophageal and gastroesophageal junction cancer.…”
Section: Biology and Chemistry Of Bryostatin-1mentioning
confidence: 99%
“…Its efficacy as a single agent has varied as a function of cancer type. More recently, studies have shown that it can enhance the clinical efficacy of known oncolytics in several cases (28)(29)(30). Additionally, bryostatin or its tunable analogs provide a starting point for promising immunotherapeutic approaches to cancer treatment (31).…”
mentioning
confidence: 99%